Methodological approaches in the design of Smart Specialization Strategy in Serbia - Kutlaca, Djuro; Zivkovic, Lazar; Popovic Pantic, Sanja Milan (Industrija, 2020)
The aim of this paper is to present two methodological approaches to the analysis of the regional potentials in the Republic of Serbia as a first out of the six-step phases of the development of Research and Innovation Strategy for Smart Specialization (RIS3). Within the quantitative analysis of regional/national context, two approaches that have been used in order to select preliminary priority areas are Location Quotient (LQ) and Multi-Criteria Decision Making (MCDM). This paper presents discussions related to challenges of implementation of a methodology for selection of priority sectors in the economy based on the use of LQ (LQ≥1.5) and use of MCDM methods for aggregation of all available indicators in order to be able to produce ranking lists of all active sectors in the Republic of Serbia. Both implemented methods are relatively simple for use and understandable; nevertheless, the use of MCDM (Ideal Point) Method could be more useful, having geometrical distance as an aggregate measure for all implemented indicators of economic, innovative and scientific potential.